A development of cultural well-being indicators at a community level - ยงย่วน, บัญญัติ; มีชาญ, สุรชัย; สุวรรณภาชน์, พชร; เจี่ยวิวรรธน์กุล, อธิวัฒน์; ย่องจีน, สุจินดา; สงศิริ, นันทนัช; จันทร์เจริญ, สุริยาพร (Journal of Liberal Arts Prince of Songkla University, 2025)
The objective of this research was to develop cultural well-being indicators at a community level in Thailand. Its sub-objectives were as follows: 1) to develop cultural well-being indicators at a community level 2) to develop a cultural well-being inventory and a manual related to how to use the cultural well-being inventory 3 ) to examine the quality of the cultural well-being inventory. The research design was research and development. The data collection was divided into 3 parts. Part 1 dealt with developing cultural wellbeing indicators using four kinds of data sources: 1 ) documents and related literature review 2) in-depth interviews with the cultural academicians, cultural experts and cultural practitioners 3) a survey of the model communities’ culture and 4) brainstorming with the cultural experts. Part 2 dealt with developing a cultural well-being inventory and a manual. Part 3 was related to an examination of quality of the cultural well-being inventory. The cultural well-being inventory was tried out in five regions. Then reliability of the inventory was analyzed. The results of the research were as follows: 1 ) Cultural well-being indicators at a community level were developed. They were divided into 5 parts: 1 . 1 ) cultural diversity respect 1 . 2) satisfaction of having the area of cultural expressions 1 . 3 ) cultural pride 1 . 4 ) satisfaction of having cultural agreement, cultural rules or cultural guidelines and 1 . 5 ) satisfaction of having the cultural network. 2 ) A cultural well-being inventory consisted of 1 5 items including its manual were developed. 3 ) The reliability of the inventory was 0.70 and it was suitable for application in communities.